A Scheffe’s Predictive Model for Modulus of Elasticity of Sawdust Ash - Sand Concrete - Kenneth Miebaka Oba; Onuegbu Okoronkwo Ugwu (International Journal of Engineering and Management Research, 2021)
The industrial waste, Saw Dust Ash (SDA) has been explored by several concrete related researches to achieve environmental and economic sustainability. In this study, 5% of sand was replaced with SDA to produce concrete with five different mix ratios. Scheffe’s simplex theory was used for five mix ratios in a 5,2 experimental design which resulted in additional ten mix ratios. For purposes of verification and testing, additional fifteen mix ratios were generated from the initial fifteen. Concrete cubes of 150mmX150mmX150mm were formed using the thirty concrete mix ratios generated, and cured in water for 28days. The compressive strengths of cubes from each mix ratio were determined. The static moduli of elasticity were also determined with a mathematical relationship. The results of the first fifteen static moduli of elasticity values were used for the calibration of the model constant coefficients, while those from the second fifteen were used for the model verification and testing using Scheffe’s simplex lattice design. A mathematical regression model was formulated from the results, with which the static moduli of elasticity were predicted. The model was then subjected to a two-tailed t-test with 5% significance, which confirms the model adequate and fit with an R2 of 0.8536. The study also revealed that SDA can be used to replace 5% of sand and promote environmental sustainability without significantly decreasing the static modulus of elasticity.